2014
DOI: 10.1371/journal.pone.0086539
|View full text |Cite
|
Sign up to set email alerts
|

Fuzi Attenuates Diabetic Neuropathy in Rats and Protects Schwann Cells from Apoptosis Induced by High Glucose

Abstract: Radix aconite lateralis preparata (Fuzi), a folk medicine, has long been used for the treatment of diabetes and paralysis in China. We examined the effect of Fuzi alone on diabetic rats and Schwann cells in high glucose and the components responsible for its activity. The major constituents of FZE were identified by HPLC-MS/MS data. Male Sprague Dawley rats (n = 36) were randomly divided into control, diabetic, FZE 1.75 g/kg, FZE 3.50 g/kg, FZE 7.00 g/kg, and methylcobalamin groups. After two weeks treatment, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 19 publications
2
25
0
Order By: Relevance
“…Exposure of Schwann cells to high glucose levels in vitro causes oxidative stress that is accompanied by over activation of caspase-9 and apoptosis regulator BAX, and decreased levels of apoptosis regulator Bcl-2 (REF. 80), changes that indicate mitochondrial internal stress. In an important study published in 2011, targeted disruption of Schwann cell mitochondria in a transgenic mouse model critically affected neuronal survival and produced a peripheral neuropathy resembling that caused by diabetes 81 .…”
Section: Oxidative Stress and Mitochondrial Dysfunctionmentioning
confidence: 99%
“…Exposure of Schwann cells to high glucose levels in vitro causes oxidative stress that is accompanied by over activation of caspase-9 and apoptosis regulator BAX, and decreased levels of apoptosis regulator Bcl-2 (REF. 80), changes that indicate mitochondrial internal stress. In an important study published in 2011, targeted disruption of Schwann cell mitochondria in a transgenic mouse model critically affected neuronal survival and produced a peripheral neuropathy resembling that caused by diabetes 81 .…”
Section: Oxidative Stress and Mitochondrial Dysfunctionmentioning
confidence: 99%
“…Fuzi extract (in a hydrochloric acid solution) protected Schwann cells from high glucose injury and apoptosis, mainly due to the alkaloids. Also, the mitochondria pathway mediates the protective effect . These studies indicate that active ingredients of Fuzi possess effects of anti‐inflammatory, anti‐anxiety, and protect nerve cells.…”
Section: Neuropharmacological Effect Of Aconiti Lateralis Radix Praepmentioning
confidence: 77%
“…However, in clinical trials, no great improvement was reported in nerve conduction velocities and despite the initial promise of gene therapy, there is still currently no treatment available that can effectively repair the damage induced by DPN [25-27]. Several traditional natural medicines have been found to relieve the symptoms of DPN through antioxidant properties and by inhibiting the apoptotic nature of SCs in hyperglycemic conditions [28, 29]. For instance, Radix aconite lateralis preparata, a traditional Chinese medicine that has long been used to treat diabetes and paralysis, is thought to inhibit the apoptotic nature of SCs in hyperglycemic conditions through mitigated glucose-induced mitochondrial dysfunction [28].…”
Section: Discussionmentioning
confidence: 99%
“…Several traditional natural medicines have been found to relieve the symptoms of DPN through antioxidant properties and by inhibiting the apoptotic nature of SCs in hyperglycemic conditions [28, 29]. For instance, Radix aconite lateralis preparata, a traditional Chinese medicine that has long been used to treat diabetes and paralysis, is thought to inhibit the apoptotic nature of SCs in hyperglycemic conditions through mitigated glucose-induced mitochondrial dysfunction [28]. Similarly, Yang et al found by measuring MDA, SOD, and GSH-Px in the sciatic nerve tissue of STZ-induced DPN rats that Tang Bi Kang another traditional Chinese medicine, could treat DPN through antioxidative and anti-inflammatory responses [29].…”
Section: Discussionmentioning
confidence: 99%